Evaluating water security across scales: diagnostics and trends - Doeffinger, T (2020)
Water security is a concept that accounts for multiple types of water-related risks and their societal impacts. It has proved to be a complex concept, which is difficult to frame and even more challenging to evaluate. This thesis aims to evaluate water security across scales and to begin to disentangle the concept’s complexity by looking at trends and relationships between water security indicators.